2017
DOI: 10.7863/ultra.16.08054
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pessary for Preventing Preterm Birth in Singleton Pregnancies With Short Cervical Length: A Systematic Review and Meta‐analysis

Abstract: Objectives-To evaluate the effectiveness of cervical pessary for preventing spontaneous preterm birth (SPTB) in singleton gestations with a second trimester short cervix.Methods-Electronic databases were searched from their inception until February 2016. We included randomized clinical trials (RCTs) comparing the use of the cervical pessary with expectant management in singletons pregnancies with transvaginal ultrasound cervical length (TVU CL) 25 mm. The primary outcome was incidence of SPTB <34 weeks. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
4

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 30 publications
2
43
1
4
Order By: Relevance
“…Different strategies have been adopted for preventing PTB, including use of progesterone, cerclage and cervical pessary, as well as lifestyle modification, such as smoking cessation, diet, aerobic exercise and nutritional supplements. The evidence supports the use of vaginal progesterone in singleton pregnancies with short cervix, while cervical cerclage seems to be beneficial only in the subgroup of singleton gestations with both prior spontaneous PTB and CL ≤ 25 mm 10 , but not in singletons without prior PTB or in multiple gestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strategies have been adopted for preventing PTB, including use of progesterone, cerclage and cervical pessary, as well as lifestyle modification, such as smoking cessation, diet, aerobic exercise and nutritional supplements. The evidence supports the use of vaginal progesterone in singleton pregnancies with short cervix, while cervical cerclage seems to be beneficial only in the subgroup of singleton gestations with both prior spontaneous PTB and CL ≤ 25 mm 10 , but not in singletons without prior PTB or in multiple gestations.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical pessary is relatively non‐invasive and easy to use, as it does not require anesthesia, it can be inserted in an outpatient clinic setting and it can be easily removed if necessary. However, published data on the use of cervical pessary are contradictory, and meta‐analyses have shown that it has no efficacy in the prevention of PTB in both singleton and multiple pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Hui et al 9 (n = 108) and Nicolaides et al 10 (n = 924) reported no significant differences in PTB or neonatal outcome 9,10 . A meta-analysis of these three RCTs showed no significant effect on sPTB or neonatal outcome of pessary use in singleton pregnancies with short mid-trimester TVS-CL compared with no pessary 13 . The results of the current RCT are consistent with those of Hui et al 9 , Nicolaides et al 10 and the meta-analysis of all three RCTs 13 .…”
Section: Discussionmentioning
confidence: 91%
“…A meta-analysis of these three RCTs showed no significant effect on sPTB or neonatal outcome of pessary use in singleton pregnancies with short mid-trimester TVS-CL compared with no pessary 13 . The results of the current RCT are consistent with those of Hui et al 9 , Nicolaides et al 10 and the meta-analysis of all three RCTs 13 . A potential reason for the lack of demonstrable effect of treatment with a pessary in our trial is that any reduction in PTB may have been due to treatment with progesterone and that there is no added benefit of pessary.…”
Section: Discussionmentioning
confidence: 91%
“…The latest 3 meta-analyses published in 2017, pessary versus expectant management in the prevention of preterm labour are those of Saccone et al, 21 in single gestations with short cervix, in twin gestations, 22 and the one published by Jim et al 23.…”
Section: What Evidence Do the Meta-analyses Show Us?mentioning
confidence: 99%